Gestão de resíduos sólidos urbanos no município de Porto da Folha-SE - Santos, Anne Grazielle Costa (2012)
The solid waste production is entirely linked to economic development and population, however, the development doesn t recognize limits, happens disorderly significant indices contributing pollution and environmental degradation. The economic model exercised since the Industrial Revolution with the disconnect of the growth of cities and the health infrastructure has enabled new sources of secular problems spreading into the environment. Among them, the solid waste configures an aggravating faced by society by involving aspects of political, social, economic, environmental and public health. In Brazil, the absence of supervision and of propositions for implementation of solid waste management resulting in poor living conditions in the poorest regions mainly. The goal of this research was to make a diagnosis of municipal solid waste management in the municipality of Porto da Folha/SE thus wished to describe the characteristics of municipal solid waste management home; evaluate the social and environmental risks resulting from inadequate management and determine the composition of the waste produced in the city. The hypothesis of question assumed that the inefficiency of urban solid waste management anticipated hiring cleaning agents and the availability of adequate facilities, while the lack of supervision and universalization of services imply social and environmental risks. The survey has a qualitative character, however the data analysis are held of interdisciplinary problem quantitatively. The methodology was divided into: bibliographical, characterization of the area under study, instruments for data collection and waste characterisation. Porto da Folha has a municipal population of 27,146 inhabitants, the municipality is bordered on the North by the State of Alagoas, in the East with Gararu West with Poço Redondo and South with the municipalities of Nossa Senhora da Glória and Monte Alegre the Sergipe. Upon completion of this study it was found that the city has urban cleaning system through the services of sweeping, collecting and transporting waste, however this system presented managerial difficulties arising from territorial distances, costs and expenditure for personnel and equipment, soas proposition suggested the Waste Management Plan that meets all of the municipality.